Influence of physical activity of the maximum aerobic power on hemo-dynamic and morpho-biochemical of change of erythrocytes of female volleyball players - B. M. Mytckan; V. P. Verbovyi; R. Ya. Chovhan; N. O. Zemska; O.F. Kryzanivskaya; S. A. Bublyk; V. B. Mocherniuk; R. I. Faichak; G.O. Pjatnichuk; S. L. Popel'; O. V. Baskevich (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose : to study types of the cardio-hemo-dynamic reaction of an organism and morpho-biochemical changes of erythrocytes of peripheral blood of female volleyball players on physical activity of the maximum aerobic power. Material : 18 female volleyball players with different qualification participated in the experiment (age - 22,0±0,6 years). It is investigated cardio-hemo-dynamic (by functional methods), functional changes (by biochemical methods) and structure of erythrocytes (by means of the scanning electronic microscopy) before and after maximum (3,5 W/kg of body mass) physical activity. Results : It is determined that the maximum physical activity causes essential changes in cardio-hemo-dynamic. Such changes depend on the morphological reorganization of peripheral blood erythrocytes (increase in the index of erythrocytes deformation) and closely correlate with biochemical changes (decrease of ATP concentration and increase of magnesium concentration in erythrocytes). It is discussed the possible mechanisms of realization of reaction features of the organism of female volleyball players to physical activity of the maximum aerobic power. Conclusions : the physical activity of the maximum aerobic power finds typological features of the cardio-hemo-dynamic reaction of the female volleyball players' organism. Such features are expressed by conformational changes of erythrocytes of peripheral blood. They depend on the concentration of separate macroelements in these cells and type of cardio-hemo-dynamic.